2012
DOI: 10.1371/journal.pone.0032412
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence in Type 2 Diabetes: The ENTRED Study 2007, a French Population-Based Study

Abstract: BackgroundAdherence to prescribed medications is a key dimension of healthcare quality. The aim of this large population-based study was to evaluate self-reported medication adherence and to identify factors linked with poor adherence in patients with type 2 diabetes in France.MethodologyThe ENTRED study 2007, a French national survey of people treated for diabetes, was based on a representative sample of patients who claimed reimbursement for oral hypoglycaemic agents and/or insulin at least three times betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
150
5
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(207 citation statements)
references
References 38 publications
31
150
5
9
Order By: Relevance
“…Patients with poor adherence showed low glycaemic control ( HbA1c >8 ) and this is similar to the results found in other researches [4].…”
Section: Discussion:-supporting
confidence: 91%
See 3 more Smart Citations
“…Patients with poor adherence showed low glycaemic control ( HbA1c >8 ) and this is similar to the results found in other researches [4].…”
Section: Discussion:-supporting
confidence: 91%
“…This study explored therapeutic adherence and the factors contributing to the adherence of diabetic patients in Jazan region. Non adherence with medication in this study was similar to the earlier finding in Egypt [7], Palestine [10], France [4], Poland [14] and Saudi Arabia [11] In Palestine study, non-compliance was divided into two categories ( 51.4 % poor compliance and 6.5 % noncompliance ) [10]. In France the non-compliance was divided into two categories also (49% medium adherence and 12% poor adherence ) [4].…”
Section: Discussion:-supporting
confidence: 88%
See 2 more Smart Citations
“…15,16 Worldwide, studies on medication adherence among diabetic patients have shown a wide variation. [17][18][19][20][21][22][23][24] In India, [25][26][27] Limited studies from Southern and Northern regions of India have documented wide variation in the medication adherence and have addressed the issues of nonadherence in diabetic patients. 21,[28][29][30][31][32][33] AIM Therefore, this study was conducted to assess the medication adherence among type II diabetic patients attending a tertiary care hospital in Navi Mumbai, India.…”
Section: Introductionmentioning
confidence: 99%